Collaboration and Ethics in Distance Learning Design - Biem, Racquel; Morrison, Dirk (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
Ethical education practices require that all students have access to quality learning resources, necessary learning supports, diverse learning strategies, and deep learning opportunities. When it comes to learning strategies and opportunities, collaborative learning practices foster deep learning through socio-cultural interactions, asserting that individual learning is limited compared to what can be learned as a community. Education systems have an ethical obligation to ensure that what is advocated for in curricula can be achieved and will be supported. Although K–12 curricula are typically rooted in collaborative approaches, many asynchronous secondary online learning courses continue to be associated with individual learning approaches. This research used insights gleaned from 35 survey responses and 18 semi-structured interviews with secondary asynchronous distance learning teachers to analyze how collaborative learning is actualized and examine barriers to its implementation. Collaborative online learning opportunities were increasingly prevalent when communities outside of the school were leveraged for experiential learning and when students were paced as a cohort. The data indicated that an increase in collaborative learning was not likely to occur unless the learning ecosystem valued online learning as equitably as face-to-face learning in terms of investment in research-based pedagogy, student support, teacher support, and teaching and learning resources. Until such time, distance learning students will be disadvantaged concerning building collaborative competence that can lead to deeper learning opportunities.